PENGEMBANGAN PROGRAM ELEMEN HINGGA - RCFEAP UNTUK ANALISIS NONLINIER BETON BERTULANG - Brahmanto, Dody
A numerical model is proposed for reinforced concrete behavior that combines some commonly accepted ideas for modeling plain concrete, reinforcement, and interaction behavior in a consistent manner. The basic idea is that the total stress that exist in a reinforced concrete element can be decomposed into individual contribution of the plain concrete, the reinforcement, and the interaction between these constituents. The constitutive model of plain concrete is derived within the plasticity theory. The reinforcement is modeled using a standard elastoplastic model, a trilinear function. The interaction between plain concrete and reinforcement is modeled using smeared method. This model is then implemented in finite element program (RCFEAP). RCFEAP can handle problem involving either plane stress or axisymmetric. The program is then compared to the experimental result and shows good result